Physiologically Based Pharmacokinetic Modeling of Central Nervous System Pharmacokinetics of CDK4/6 Inhibitors to Guide Selection of Drug and Dosing Regimen for Brain Cancer Treatment. Issue 2 (14th September 2020) - Li, Jing; Jiang, Jun; Wu, Jianmei; Bao, Xun; Sanai, Nader
Abstract : A better understanding of the human central nervous system (CNS) pharmacokinetics is critical to the selection of the right drug and refinement of dosing regimen for more effective treatment of primary and metastatic brain cancer. Using the physiologically‐based pharmacokinetic (PBPK) modeling approach, we systematically compared the CNS pharmacokinetics of three cyclin D‐cyclin dependent kinase 4 and 6 (CDK4/6) inhibitors (ribociclib, palbociclib, and abemaciclib) in patients with cancer. A PBPK model platform was developed and verified for predicting plasma and CNS pharmacokinetics. Target engagement ratio (TER), defined as the ratio of the average steady‐state unbound drug brain concentration to the in vitro half‐maximal inhibitory concentration (IC50 ) for CDK4/6 inhibition, was used as a crude predictor of efficacy. As compared with ribociclib and palbociclib, abemaciclib penetrated into the human brain to a larger extent, but at a slower rate, and was retained in the brain longer. Following the standard dosing regimens, the predicted CDK4/6 TERs were 26/5.2 for abemaciclib, 2.4/0.62 for ribociclib, and 0.36/0.27 for palbociclib. Simulations suggested that abemaciclib achieved comparable TERs following twice daily or daily dosing; ribociclib may sufficiently inhibit both CDK4 and CDK6 at the maximum tolerated dose; whereas, palbociclib achieved TERs < 0.5 even at a dose 50% higher than the standard dose. In conclusion, the PBPK modeling, supported by available preclinical and clinical evidence, suggests that abemaciclib is the best CDK4/6 inhibitor for brain cancer treatment, whereas palbociclib is not recommended. The model refined dosing regimen is 300 mg daily on a 4‐weeks‐on schedule for abemaciclib, and 900 mg daily on a 3‐weeks‐on/1‐week‐off schedule for ribociclib.